Analisis Kelayakan Usaha Home Industry Keripik Gadung dengan Pendekatan Finansial di Desa Made Kecamatan Kudu Kabupaten Jombang - Pranata, Muhamad Iin; Nur Qomariyah, Umi Kulsum (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2020)
The purpose of the research to determine the level of income and feasibility in terms of the R/C Ratio in the Home Industry business of gadung chips in Waru Hamlet, Made Village, Kudu District, Jombang Regency. The selection of research locations was carried out by purposive sampling. This study uses primary data and secondary data. Primary data obtained from the field through interviews with respondents directly and observations (observations) in the field. Secondary data obtained from agencies related to the problem and object under study. The analysis used includes analysis of costs, revenues, revenues and R/C Ratio. The results of the Home Industry research, Mr. Sunaryo's gadung chips business during 2018-2020 earned an income of Rp. 20,999,000 with details of income in 2018 of Rp.8,513,000, in 2019 of 8,383,000 and in 2020 income of Rp. 4,103,000. The value of business feasibility in terms of the R/C Ratio in 2018 is 1.3, in 2019 1.3, in 2020 the value of the R/C Ratio is 1.1, while the calculation of the total value of the R/C Ratio from 2018 - 2020 is equal to 1.3. The results of this R/C Ratio value both annually and in total from 2018 - 2020 are in accordance with the criteria if the R/C Ratio value > 1 then the business is feasible to be developed. Thus, Sunaryo's gadung chips Home Industry business in Waru/kedungwatu Hamlet, Made Village, Kudu District, Jombang Regency is profitable and feasible for business development.